Photoacoustic tomography imaging and estimation of oxygen saturation of hemoglobin in ocular tissue of rabbits. (September 2015) - Hennen, Stella N.; Xing, Wenxin; Shui, Ying-Bo; Zhou, Yong; Kalishman, Jennifer; Andrews-Kaminsky, Lisa B.; Kass, Michael A.; Beebe, David C.; Maslov, Konstantin I.; Wang, Lihong V.
Abstract: This study evaluated in vivo imaging capabilities and safety of qualitative monitoring of oxygen saturation of hemoglobin ( s O2 ) of rabbit ciliary body tissues obtained with acoustic resolution (AR) photoacoustic tomography (PAT). AR PAT was used to collect trans-scleral images from ciliary body vasculature of seven New Zealand White rabbits. The PAT s O2 measurements were obtained under the following conditions: when systemic s O2 as measured by pulse oximetry was between 100% and 99% (level 1); systemic s O2 as measured by pulse oximetry was between 98% and 90% (level 2); and systemic s O2 as measured by pulse oximetry was less than 90% (level 3). Following imaging, histological analysis of ocular tissue was conducted to evaluate for possible structural damage caused by the AR PAT imaging. AR PAT was able to resolve anatomical structures of the anterior segment of the eye, viewed through the cornea or anterior sclera. Histological studies revealed no ocular damage. On average, s O2 values (%) obtained with AR PAT were lower than s O2 values obtained with pulse oximetry (all p < 0.001): 86.28 ± 4.16 versus 99.25 ± 0.28, 84.09 ± 1.81 vs. 95.3 ± 2.6, and 64.49 ± 7.27 vs. 71.15 ± 10.21 for levels 1, 2 and 3 respectively. AR PAT imaging modality is capable of qualitative monitoring for deep tissue s O2 in rabbits. Further studies are needed to validate and modify the AR PAT modality specifically for use in human eyes. Having a safe, non-invasive method of in vivo imaging of s O2 in the anterior segment is important to studies evaluating the role of oxidative damage, hypoxia and ischemia in pathogenesis of ocular diseases. Highlights: We used acoustic resolution (AR) photoacoustic tomography (PAT) and pulse oximetry. s O2 was measured in rabbit ciliary body tissue. AR PAT s O2 were lower than SPO s O2 values. Further studies are need to validate our initial results.